Dynamic observation of dual-beam irradiated Fe and Fe-10Cr alloys at 435 °C. (1st May 2021) - Lin, Yan-Ru; Chen, Wei-Ying; Li, Meimei; Henry, Jean; Zinkle, Steven John
Abstract: The attractive mechanical properties and superior resistance to void-swelling make ferritic/martensitic alloys a promising structural material for advanced nuclear reactors. However, one anomaly that has intrigued researchers for more than 50 years is the proportion of two types of dislocation loops in Fe and Fe-Cr alloys with Burger vectors b =½<111> and b =<100>. Although the possible mechanisms responsible for the presence of 〈100〉 loops continue to be the subject of intense modeling studies, there remains incomplete experimental understanding of fundamental irradiation processes in Fe(Cr) alloys. Here, the dose dependence of the irradiation-induced microstructural evolution was examined from 0 to 20 displacement per atom (dpa) in high purity Fe and Fe-10Cr during simultaneous dual-beam (1 MeV Kr + 10 appm He/dpa) irradiation at 435 °C. We experimentally revealed that the mechanism for the formation of 〈100〉 loops may not follow the conventional simple dislocation reaction between two ½<111> loops. Real-time dynamic formation and evolution of defects including black dot loops, loop coarsening, loop decoration, network dislocations, and cavities were demonstrated. Several results indicated that the addition of Cr and He could impede dislocation loop motion. The evolution of the defect size/density and relative fraction of ½<111> vs 〈100〉 loops were quantitatively summarized. With increasing dose, ½<111> loops became the dominant type of loop in both materials. Notably, 〈100〉 loops were predominantly observed near grain boundaries only for pure Fe, while arrays of nanoscale black dot defects composing the 〈100〉 loop strings were observed in plenty in Fe-10Cr. Graphical abstract: Image, graphical abstract